Factors Affecting The Development Of Shenzhen As A Global City In Innovation And R&D Activities - Jiaxiong, Huang (2024)
Innovation become a powerful engine for sustain and promote regional competitiveness. To explores regional innovation performance and prosperity is crucial achieve balanced regional development. It is challenging to explore the contributions of local condition factors to city innovation. This research constructs a framework for research on associations with innovation from a global city’s perspective. It aims to analyse the affect factors of city innovation and respond to the limitations of existing studies. An ICT industry is used to case study in Shenzhen, China, in the East Asia region. The primary and secondary data were used to explore the effect of Stakeholder geographic distance and cooperative and government intervention on innovation. The results show that the effect factors affecting the innovation and R&D capacity of global cities emphasize the importance of geographical proximity of stakeholders, collaborative links, and local government interventions. The research emphasizes that the innovation achievements and prosperity of global cities are the result of the interaction of stakeholders with local conditions (a series of resources of expertise, skills, physical facilities, and funding). The international connectivity of global cities in innovation is considered the collaborative link between multinational companies and local innovation stakeholders. However, local and multinational firms differ in their use and share these resources, the most fundamental difference is the influence of corporate strategy, collaborative networks, and social capital on the configuration of the innovation and R&D process.